Predictors of Central Student Learning Outcomes in Times of COVID-19: Students’, Parents’, and Teachers’ Perspectives During School Closure in 2020—A Multiple Informant Relative Weight Analysis - Helm, Christoph; Huber, Stephan Gerhard (Frontiers in Education, 2022)
School closures associated with the COVID-19 pandemic very quickly led to many studies on distance education. Currently, there are only studies available that explored the importance of different features of distance education for student learning during school lockdowns in 2020 relying on a single perspective—student, parent, or teacher data. Thus, we present results from a multiple informant study in which we compared prediction models based on the different perspectives of relevant actors in the school system. Against the background of the context, input, process, and output model, we explored the impact of a broad range of features of distance education on central student learning outcomes using data from students (N = 315), parents (N = 518), and teachers (N = 499) in German and Austrian secondary schools. Although findings from relative weight analysis portray a relatively similar pattern of relevant predictors for students’ learning outcomes (i.e., self-rated achievement, learning effort, and intrinsic motivation) across the three respondent groups, some predictors largely differ between the groups. While students’ ability to self-organize emerged as the most significant predictor across all three informant groups, predictors, such as the lack of parental support during school closure, turned out to be relevant only from parents’ perspective. We discuss the implications of these findings for future educational practice and research.